(untitled) (Journal of Human Sciences, 2021)
The lack of translation from the Ottoman language created a ‎knowledge ‎vacuum for a significant period in the history of Libya, as a ‎result of the ‎lack of translation work due to the difficulty of translating ‎from Ottoman ‎documents, and the lack of dealing with their texts due to ‎the absence of ‎translation. Fezzan region and the southern ‎desert regions from ‎(Borno_Kanem_‎ ‎‎‎‎‎Sokoto_‎ Aqdaz‎_‎ ‎‎ Timbuktu_wadai_Ghat_Ghadames) r‎egio‎ns have a history, ‎deserve ‎a lot of research and study. This research is a translation of a document related to Fezzan ‎‎region in the second Ottoman era, which was published in ‎‎documents related to the history of Sudan in the Ottoman era, perhaps ‎‎including some information that would benefit specialists in the ‎ ‎history of ‎Libya.